The impact of cooking and burial on proteins: a characterisation of experimental foodcrusts and ceramics - Evans, Miranda; Hagan, Richard; Bondetti, Manon; Boyd, Oliver; Craig, Oliver E; Collins, Matthew J; Hendy, Jessica (The Royal Society, 2024)
Peer reviewed: True Publication status: Published Funder: H2020 European Research Council; FundRef: http://dx.doi.org/10.13039/100010663 Funder: Newnham College, University of Cambridge; FundRef: http://dx.doi.org/10.13039/501100000663 Funder: Cambridge Trust; FundRef: http://dx.doi.org/10.13039/501100003343 Funder: H2020 Marie Skłodowska-Curie Actions; FundRef: http://dx.doi.org/10.13039/100010665 Funder: Leverhulme Trust; FundRef: http://dx.doi.org/10.13039/501100000275 Foodcrusts have received relatively little attention in the burgeoning field of proteomic analysis of ancient cuisine. We remain ignorant of how cooking and burial impact protein survival, and crucially, the extent to which the extractome reflects the composition of input ingredients. Therefore, through experimental analogues we explore the extent of protein survival in unburied and buried foodcrusts and ceramics using ‘typical’ Mesolithic ingredients (red deer, Atlantic salmon and sweet chestnut). We then explore a number of physicochemical properties theorised to aid protein preservation. The results reveal that proteins were much more likely to be detected in foodcrusts than ceramics using the methodology employed, input ingredient strongly influences protein preservation, and that degradation is not universal nor linear between proteins, indicating that multiple protein physicochemical properties are at play. While certain properties such as hydrophobicity apparently aid protein preservation, none single-handedly explain why particular proteins/peptides survive in buried foodcrusts: this complex interplay requires further investigation. The findings demonstrate that proteins indicative of the input ingredient can be identifiable in foodcrust, but that the full proteome is unlikely to preserve. While this shows promise for the survival of proteins in archaeological foodcrust, further research is needed to accurately interpret foodcrust extractomes. This project has received funding from the European Union's EU Framework ...